The Health Impact of Adult Cervical Deformity in Patients Presenting for Surgical Treatment: Comparison to United States Population Norms and Chronic Disease States Based on the EuroQuol‐5 Dimensions Questionnaire. Issue 5 (May 2017) - Smith, Justin S.; Line, Breton; Bess, Shay; Shaffrey, Christopher I.; Kim, Han Jo; Mundis, Gregory; Scheer, Justin K.; Klineberg, Eric; O'Brien, Michael; Hostin, Richard; Gupta, Munish; Daniels, Alan; et al.
Abstract : BACKGROUND: : Although adult cervical spine deformity (ACSD) is associated with pain and disability, its health impact has not been quantified in comparison to other chronic diseases. OBJECTIVE: : To perform a comparative analysis of the health impact of symptomatic ACSD to US normative and chronic disease values using EQ‐5D (EuroQuol‐5 Dimensions questionnaire) scores. METHODS: : ACSD patients presenting for surgical treatment were identified from a prospectively collected multicenter database. Baseline demographics and EQ‐5D scores were collected and compared with US normative and disease state values. RESULTS: : Of 121 ACSD patients, 115 (95%) completed the EQ‐5D (60% women, mean age 61 years, previous spine surgery in 44%). Diagnoses included kyphosis with mid‐cervical (63.4%), cervico‐thoracic (23.5%), or thoracic (8.7%) apex and primary coronal deformity (4.3%). The mean ACSD EQ‐5D index was 0.511 (standard definition = 0.224), which is 34% below the bottom 25th percentile (0.780) for similar age‐ and gender‐matched US normative populations. Mean ACSD EQ‐5D index values were worse than the bottom 25th percentile for several other disease states, including chronic ischemic heart disease (0.708), malignant breast cancer (0.708), and malignant prostate cancer (0.708). ACSD mean index values were comparable to the bottom 25th percentile values for blindness/low vision (0.543), emphysema (0.508), renal failure (0.506), and stroke (0.463). EQ‐5D scores did not significantly differ based on cervical deformity type ( P = .66). CONCLUSION: : The health impact of symptomatic ACSD is substantial, with negative impact across all EQ‐5D domains. The mean ACSD EQ‐5D index was comparable to the bottom 25th percentile values for blindness/low vision, emphysema, renal failure, and stroke.